Morphological and phenological shoot plasticity in a Mediterranean evergreen oak facing long-term increased drought. - Limousin, Jean-Marc; Rambal, Serge; OURCIVAL, JEAN-MARC; Rodriguez-Calcerrada, Jesus; Pérez-Ramos, Ignacio M; Rodríguez-Cortina, Raquel; Misson, Laurent; Joffre, Richard (Oecologia, 2012)
Mediterranean trees must adjust their canopy leaf area to the unpredictable timing and severity of summer drought. The impact of increased drought on the canopy dynamics of the evergreen Quercus ilex was studied by measuring shoot growth, leaf production, litterfall, leafing phenology and leaf demography in a mature forest stand submitted to partial throughfall exclusion for 7 years. The leaf area index rapidly declined in the throughfall-exclusion plot and was 19% lower than in the control plot after 7 years of treatment. Consequently, leaf litterfall was significantly lower in the dry treatment. Such a decline in leaf area occurred through a change in branch allometry with a decreased number of ramifications produced and a reduction of the leaf area supported per unit sapwood area of the shoot (LA/SA). The leafing phenology was slightly delayed and the median leaf life span was slightly longer in the dry treatment. The canopy dynamics in both treatments were driven by water availability with a 1-year lag: leaf shedding and production were reduced following dry years; in contrast, leaf turnover was increased following wet years. The drought-induced decrease in leaf area, resulting from both plasticity in shoot development and slower leaf turnover, appeared to be a hydraulic adjustment to limit canopy transpiration and maintain leaf-specific hydraulic conductivity under drier conditions.
Keywords: allometry; Dehydration; Droughts; France; leaf area; leaf demography; litterfall; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: physiology; Plant Shoots; Plant Shoots: growth & development; Quercus; Quercus: physiology; shoot growth; Trees

Morphological and phenological shoot plasticity in a Mediterranean evergreen oak facing long-term increased drought. - Limousin, Jean-Marc; Rambal, Serge; OURCIVAL, JEAN-MARC; Rodriguez-Calcerrada, Jesus; Pérez-Ramos, Ignacio M.; Rodríguez-Cortina, Raquel; Misson, Laurent; Joffre, Richard (Oecologia, 2012)
Mediterranean trees must adjust their canopy leaf area to the unpredictable timing and severity of summer drought. The impact of increased drought on the canopy dynamics of the evergreen Quercus ilex was studied by measuring shoot growth, leaf production, litterfall, leafing phenology and leaf demography in a mature forest stand submitted to partial throughfall exclusion for 7 years. The leaf area index rapidly declined in the throughfall-exclusion plot and was 19% lower than in the control plot after 7 years of treatment. Consequently, leaf litterfall was significantly lower in the dry treatment. Such a decline in leaf area occurred through a change in branch allometry with a decreased number of ramifications produced and a reduction of the leaf area supported per unit sapwood area of the shoot (LA/SA). The leafing phenology was slightly delayed and the median leaf life span was slightly longer in the dry treatment. The canopy dynamics in both treatments were driven by water availability with a 1-year lag: leaf shedding and production were reduced following dry years; in contrast, leaf turnover was increased following wet years. The drought-induced decrease in leaf area, resulting from both plasticity in shoot development and slower leaf turnover, appeared to be a hydraulic adjustment to limit canopy transpiration and maintain leaf-specific hydraulic conductivity under drier conditions.
The following values have no corresponding Zotero field: accession-num: 22159896
Keywords: allometry; Dehydration; Droughts; France; leaf area; leaf demography; litterfall; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: physiology; Plant Shoots; Plant Shoots: growth & development; Quercus; Quercus: physiology; shoot growth; Trees

Adaptive strategy at the leaf level of Arbutus unedo L. to cope with Mediterranean climate - Gratani, Loretta; Ghia, Emanuela (Flora-Morphology, Distribution, Functional Ecology of …, 2002)
The adaptive strategy of Arbutus unedo L. under Mediterranean climate seemed to be due to the high leaf area (LA = 11.1 ± 0.1 cm2 ) increasing the potential capacity of light interception, the high leaf lamina thickness (L = 395 ± 10 µm) increasing the potential capacity for gas exchange, and the steeper leaf inclination at midday (α up to 63.9 ± 0.3°) determining 48% of reduction of incident radiation on a sloping leaf surface (RI), which could be a prevention mechanism against the potential photoinhibition of water-stressed leaves during drought. Nevertheless, during the drought period the photosynthetic activity and the water use efficiency (WUE) of A. unedo were strongly reduced (≥ than 50% of the maximum). Principal component analysis (PCA) underlined the higher similarity of A. unedo and Quercus ilex L. from a physiological point of view (photosynthetic rates PN , transpiration rates E, stomatal conductance gs , sub-stomatal CO2 concentration Ci ) and for leaf inclination, and with Cistus incanus L. from a phenological (leaf-life span) and structural point of view (specific leaf area SLA and leaf tissue density LTD), for leaf temperature (Tl ) and for leaf water status (leaf water potential at midday Ψmin and relative water content RWC). Therefore A. unedo might be considered in the borderline between drought semi-deciduous species and evergreen sclerophyllous species.
Keywords: Gas exchange; leaf area; leaf inclination; leaf lamina thickness; leaf-life span; sclerophylly

Adaptive strategy at the leaf level of Arbutus unedo L. to cope with Mediterranean climate - Gratani, Loretta; Ghia, Emanuela (Flora-Morphology, Distribution, Functional Ecology of …, 2002)
The adaptive strategy of Arbutus unedo L. under Mediterranean climate seemed to be due to the high leaf area (LA = 11.1 ± 0.1 cm2 ) increasing the potential capacity of light interception, the high leaf lamina thickness (L = 395 ± 10 µm) increasing the potential capacity for gas exchange, and the steeper leaf inclination at midday (α up to 63.9 ± 0.3°) determining 48% of reduction of incident radiation on a sloping leaf surface (RI), which could be a prevention mechanism against the potential photoinhibition of water-stressed leaves during drought. Nevertheless, during the drought period the photosynthetic activity and the water use efficiency (WUE) of A. unedo were strongly reduced (≥ than 50% of the maximum). Principal component analysis (PCA) underlined the higher similarity of A. unedo and Quercus ilex L. from a physiological point of view (photosynthetic rates PN , transpiration rates E, stomatal conductance gs , sub-stomatal CO2 concentration Ci ) and for leaf inclination, and with Cistus incanus L. from a phenological (leaf-life span) and structural point of view (specific leaf area SLA and leaf tissue density LTD), for leaf temperature (Tl ) and for leaf water status (leaf water potential at midday Ψmin and relative water content RWC). Therefore A. unedo might be considered in the borderline between drought semi-deciduous species and evergreen sclerophyllous species.
Keywords: Gas exchange; leaf area; leaf inclination; leaf lamina thickness; leaf-life span; sclerophylly

Análisis del área foliar del alcornoque en relación con tratamientos silvo-pastorales - Caritat, A. I.; Molinas, M. I.; Vilar, I. P.; Masson, L. (Scientia gerundensis, 1999)
The fluctuations showed by ecophysiologic parameters, like leaf area and leaf area indices, in relation to silvo-pastoral treatments can be used to evaluate the effects of these treatments on o&-cork forests. Leaf area shows a close relation to production and is a good indicator of the physiological state of the plants. Leaf area, leaf area indices and specific leaf weight have been studied in four cork-oak wood stations in relation to shrub clearing and grazing treat- ments. Leaf parameters have been measured using a computer image analysis system. We found that, in general, leaf average area is increased by silvo-pastotal treatments, apparently in order to recover the wasted canopy and in answer to nutrient supply. On the other hand, leaf area index decreases after treatments because of the leaf biomass lost, but the fast apical growth showed by cork-trees in treated plots points to a quick recovery of this parameter when an appropiate tree density is reached.
Keywords: cork-oak; Grazing; leaf area; leaf index; shrub cleareing; silvo-pastoral treatments

Análisis del área foliar del alcornoque en relación con tratamientos silvo-pastorales - Caritat, A I; Molinas, M I; Vilar, I P; Masson, L (Scientia gerundensis, 1999)
The fluctuations showed by ecophysiologic parameters, like leaf area and leaf area indices, in relation to silvo-pastoral treatments can be used to evaluate the effects of these treatments on o&-cork forests. Leaf area shows a close relation to production and is a good indicator of the physiological state of the plants. Leaf area, leaf area indices and specific leaf weight have been studied in four cork-oak wood stations in relation to shrub clearing and grazing treat- ments. Leaf parameters have been measured using a computer image analysis system. We found that, in general, leaf average area is increased by silvo-pastotal treatments, apparently in order to recover the wasted canopy and in answer to nutrient supply. On the other hand, leaf area index decreases after treatments because of the leaf biomass lost, but the fast apical growth showed by cork-trees in treated plots points to a quick recovery of this parameter when an appropiate tree density is reached.
Keywords: cork-oak; Grazing; leaf area; leaf index; shrub cleareing; silvo-pastoral treatments

Rhythmic growth rings of wood and their relationship with the foliage in oak seedlings grown in a favourable environment - MANSOUR, A; de FAŸ, E (Annals of botany, 1998)
{{The anatomy of wood was studied in Quercus robur L. and Quercus suber L. seedlings exhibiting 3±8 units of extension, each with a tier of photosynthesizing leaves in their upper parts, generated as the result of rhythmic shoot growth under favourable conditions. At all the axis levels examined (i.e. the base of each of the diﬀerent units of extension, four other equidistant levels within the ®rst unit of extension and the upper part of the taproot), the wood displayed rings when treated with Wiesner reagents. This indicated cinnamaldehyde groups present in lignins. No rings appeared when the Mau$le reaction was used for speci®c detection of syringyl subunits in lignins. A trend towards a periodical arrangement of xylem parenchyma bands was also found when sections were treated with I # }KI. The number of rings coincided with the number of leaf tiers above the level of measurement, and did not vary inside the ®rst unit of extension. Thus, the rings are called rhythmic growth rings. In sections of the ®rst and the second units of extension, and in the taproot, the area and width of a given rhythmic growth ring were highly correlated with the total area of leaves present above the level of measurement at the presumed time of growth ring formation. Moreover, stem diameter at the base of the units of extension was highly correlated with the leaf area above. These results indicate that diﬀerentiation of xylem, particularly its ligni®cation, varies rhythmically in oak seedlings. They imply that wood production is linked to the photosynthesizing and}or transpiring area of the plant. Thus, during a growth cycle of Q. robur and Q. suber seedlings, there appears to be integration of the primary metabolic activities with the laying down of rhythmic growth rings
Keywords: allometric relationship; juvenile wood; leaf area; lignification; oak seedling; periodic structure; quercus robur l; Quercus Suber L; rhythmic growth ring; unit of extension

Rhythmic growth rings of wood and their relationship with the foliage in oak seedlings grown in a favourable environment - MANSOUR, A.; de FAŸ, E. (Annals of botany, 1998)
{{The anatomy of wood was studied in Quercus robur L. and Quercus suber L. seedlings exhibiting 3±8 units of extension, each with a tier of photosynthesizing leaves in their upper parts, generated as the result of rhythmic shoot growth under favourable conditions. At all the axis levels examined (i.e. the base of each of the diﬀerent units of extension, four other equidistant levels within the ®rst unit of extension and the upper part of the taproot), the wood displayed rings when treated with Wiesner reagents. This indicated cinnamaldehyde groups present in lignins. No rings appeared when the Mau$le reaction was used for speci®c detection of syringyl subunits in lignins. A trend towards a periodical arrangement of xylem parenchyma bands was also found when sections were treated with I # }KI. The number of rings coincided with the number of leaf tiers above the level of measurement, and did not vary inside the ®rst unit of extension. Thus, the rings are called rhythmic growth rings. In sections of the ®rst and the second units of extension, and in the taproot, the area and width of a given rhythmic growth ring were highly correlated with the total area of leaves present above the level of measurement at the presumed time of growth ring formation. Moreover, stem diameter at the base of the units of extension was highly correlated with the leaf area above. These results indicate that diﬀerentiation of xylem, particularly its ligni®cation, varies rhythmically in oak seedlings. They imply that wood production is linked to the photosynthesizing and}or transpiring area of the plant. Thus, during a growth cycle of Q. robur and Q. suber seedlings, there appears to be integration of the primary metabolic activities with the laying down of rhythmic growth rings
Keywords: allometric relationship; juvenile wood; leaf area; lignification; oak seedling; periodic structure; quercus robur l; Quercus Suber L; rhythmic growth ring; unit of extension

Morphological adjustments of mature Quercus ilex trees to elevated CO 2 - Hättenschwiler, S; Miglietta, Franco; Raschi, Antonio; Körner, C (Acta Oecologica, 1997)
It is still not known whether mature forest trees respond to increasing atmospheric CO 2 concen- trations in similar ways as seedlings do. Mature Mediterranean oaks (Qaercus ilex) growing in a CO 2 enriched atmosphere around natural CO 2 vents since the seedling stage showed a moderate, age- dependent increase in stem biomass production, but had significantly lower biomass of 6-year-old branches, decreased branching, and lower leaf area per unit branch biomass, compared to control trees at a nearby unenriched site. Our data indicate that trees in natural forest stands morphologically adjust to increasing CO 2 and reduce COz-induced initial growth stimulations. Allometric adjustments such as reduction in leaf area may be regarded as a "down-regulation" of canopy photosynthesis and may be an effective mechanism for saving water.
Keywords: allometric adjustments; biomass allocation; branch morphology; branching; leaf area; Mediterranean; natural co 2 springs; Quercus ilex

Morphological adjustments of mature Quercus ilex trees to elevated CO 2 - Hättenschwiler, S.; Miglietta, Franco; Raschi, Antonio; Körner, C. (Acta Oecologica, 1997)
It is still not known whether mature forest trees respond to increasing atmospheric CO 2 concen- trations in similar ways as seedlings do. Mature Mediterranean oaks (Qaercus ilex) growing in a CO 2 enriched atmosphere around natural CO 2 vents since the seedling stage showed a moderate, age- dependent increase in stem biomass production, but had significantly lower biomass of 6-year-old branches, decreased branching, and lower leaf area per unit branch biomass, compared to control trees at a nearby unenriched site. Our data indicate that trees in natural forest stands morphologically adjust to increasing CO 2 and reduce COz-induced initial growth stimulations. Allometric adjustments such as reduction in leaf area may be regarded as a "down-regulation" of canopy photosynthesis and may be an effective mechanism for saving water.
Keywords: allometric adjustments; biomass allocation; branch morphology; branching; leaf area; Mediterranean; natural co 2 springs; Quercus ilex

RESPONSE TO MICROCLIMATE OF MORPHOLOGICAL LEAF ATTRIBUTES, PHOTOSYNTHETIC AND WATER RELATIONS OF EVERGREEN SCLEROPHYLLOUS SHRUB SPECIES - Gratani, L (PHOTOSYNTHETICA, 1993)
Leaf adaptations of Quercus ilex L., Phillyrea latifolia L. and Pistacia lentiscus L. to various environmental conditions namely from the viewpoint of the differences of leaf area, dry mass, chlorophyll (Chl) content, sclerophylly index, succulence index and net photosynthetic rate (P(N)), are shown. Irradiance was the most important factor to influence P(N), leaf temperature, stomatal conductance (g(s) and transpiration rate (E). Under canopy layer low red-far red ratio reduced P(N). Shade leaves were enriched by Chl b. Chl content and sclerophylly index were good leaf characteristics to express adaptability of plants to microclimate.
Keywords: irradiance; leaf area; microclimate; Phillyrea latifolia L.; Pistacia lentiscus L.; Quercus ilex L.

RESPONSE TO MICROCLIMATE OF MORPHOLOGICAL LEAF ATTRIBUTES, PHOTOSYNTHETIC AND WATER RELATIONS OF EVERGREEN SCLEROPHYLLOUS SHRUB SPECIES - GRATANI, L. (PHOTOSYNTHETICA, 1993)
Leaf adaptations of Quercus ilex L., Phillyrea latifolia L. and Pistacia lentiscus L. to various environmental conditions namely from the viewpoint of the differences of leaf area, dry mass, chlorophyll (Chl) content, sclerophylly index, succulence index and net photosynthetic rate (P(N)), are shown. Irradiance was the most important factor to influence P(N), leaf temperature, stomatal conductance (g(s) and transpiration rate (E). Under canopy layer low red-far red ratio reduced P(N). Shade leaves were enriched by Chl b. Chl content and sclerophylly index were good leaf characteristics to express adaptability of plants to microclimate.
The following values have no corresponding Zotero field: pub-location: NA KARLOVCE 1A, PRAGUE 6, CZECH REPUBLIC CS-160 00 publisher: INST EXPERIMENTAL BOTANY, ACAD SCI CZECH REPUBLIC
Keywords: irradiance; leaf area; microclimate; Phillyrea latifolia L.; Pistacia lentiscus L.; Quercus ilex L.